Development of a Program for Visualization of Data From Sensor MPU6050 in Python for Mobile Robots - Yevsieiev, V. (European Scientific Platform, 2023)
The MPU6050 sensor is a device that combines a gyroscope and an accelerometer and allows you to determine the orientation and movement of an object in space. For mobile robots, such a sensor can be very useful as it can provide information about the current position and movement of the robot.
Keywords: gyroscope; program Python; mobile robots; Raspberry Pi OS; accelerometer